Librarians and engineering faculty: Partnership opportunities in information literacy and ethics instruction - Trussell, Alice (My University, 2004)
As the global economy grew in the latter half of the 20th Century, the demand for the mobility of engineers greatly increased. In the 1980’s and 1990’s, the Accreditation Board for Engineering and Technology (ABET), an accreditation agency serving primarily the United States, began to look at engineering programs outside of the United States with the intent of establishing recognized reciprocity. Through the Washington Accord, first established in 1989, mutual recognition agreements were signed with accrediting agencies in several countries. In the year 2000, heavily modified ABET standards affecting North America took effect emphasizing qualitative standards as well as quantitative ones. One aspect of the enhanced criteria that is particularly relevant to engineering and technology libraries is “an understanding of ethical and professional responsibility”. Librarians have been providing essential instruction in ethics for many years through lessons in Information Literacy. Librarians can assist technological university administrations in adjusting to the emerging standards by partnering with faculty to incorporate lessons of ethical and professional responsibility into curricula.
Keywords: ABET 2000; Accreditation reciprocity; Ethics; Information literacy; Instruction; Plagiarism